1989
DOI: 10.3109/00365548909035679
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Pathogenic Microorganisms in the Oral Cavity during Febrile Episodes in Immunocompromised Patients with Haematologic Malignancies

Abstract: The purpose of the study was to describe the occurrence of potentially pathogenic microorganisms during febrile episodes in haematologic patients, who had been treated with anti-neoplastic drugs within the previous 4 weeks. During a 9-month period 78 consecutive febrile episodes occurred in 46 patients who were examined daily. On day 1, before antibiotic treatment was started, members of the normal flora were found in 83%, Candida spp. in 72%, Enterobacteriaceae in 29%, Pseudomonas aeruginosa in 8%, Staphyloco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Previous studies have suggested that the oral carriage of bacteria causing pneumonia such as K. pneumoniae, Pseudomonas spp., and Staphylococcus spp. is low in healthy subjects, and higher in immunodeficient and myelo-suppressed subjects [20][21][22] and also in patients with severe periodontal disease [23,24]. The significantly higher prevalence of these bacteria in the elderly requiring care is of interest, as they may be at greater risk of developing systemic disease such as pneumonia and heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the oral carriage of bacteria causing pneumonia such as K. pneumoniae, Pseudomonas spp., and Staphylococcus spp. is low in healthy subjects, and higher in immunodeficient and myelo-suppressed subjects [20][21][22] and also in patients with severe periodontal disease [23,24]. The significantly higher prevalence of these bacteria in the elderly requiring care is of interest, as they may be at greater risk of developing systemic disease such as pneumonia and heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients with severe diseases such as acute pancreatitis, inflammatory bowel disease, and infection with HIV or AIDS suffer an unacceptably high rate of opportunistic infections. In haematological malignancies, infections constitute the leading cause of morbidity, and 85% of these infections are caused by only a few families of microorganisms, for example, Enterobacteriaceae, Pseudomonaceae, and Micrococcae 13. These potentially pathogenic microorganisms (PPMs) occur normally in healthy individuals as a subflora in the GI tract, but can become dominant by overgrowth in sick patients, especially after antibiotic treatment.…”
Section: Nosocomial Infections—a Remaining Threatmentioning
confidence: 99%
“…According to a sampling method described previously (13), a cotton swab sample was obtained from all patients on each day of the investigation period in order to compare the qualitative composition of the aerobic and facultatively anaerobic oral microflora in febrile episodes with and without the presence of intraoral ulcers. All microbiological samples were taken by the same person.…”
Section: Diagnosticmentioning
confidence: 99%